Thermal rejuvenation of tellurite glasses by cooling from the supercooled liquid state at low rates. (September 2020) - Afonin, G.V.; Zamyatin, O.A.; Zamyatina, E.V.; Khonik, V.A.
Graphical abstract: Abstract: It is shown that cooling of two tellurite glasses from the supercooled liquid state to room temperature at rates of a few Kelvin per minute results in the rejuvenation (recovery) of their excess enthalpy lost upon the preceding ageing below the glass transition. The sensitivity of the rejuvenation to the cooling rate is determined and compared with that for a metallic and oxide glass.